A high flame-retardant cable protection tube and a preparation method thereof
Patent Information
- Application Number
- CN202611053907.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-13
AI Technical Summary
[0008]本发明所要解决的技术问题是:提供一种以茂金属聚烯烃为核心组分的高阻燃电缆保护管及其制备方法,以解决现有高填充阻燃聚烯烃电缆保护管中阻燃性能与力学韧性难以兼顾、阻燃剂分散性差、双层管材界面结合不稳定以及膨胀型阻燃组分在长时间高剪切加工中容易结构受损的问题
[0022]与现有技术相比,本发明提供了一种高阻燃电缆保护管及其制备方法,具备以下有益效果:通过将管材设计为承力内层与阻燃外层的共挤复合结构,使承力内层主要承担管材的力学支撑功能,使阻燃外层主要承担阻燃防护功能,避免了传统单层阻燃管材中阻燃剂高填充导致整个管壁韧性下降的问题。
Smart Images

Figure CN122896491A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable protection pipes and flame-retardant polyolefin composite materials, and particularly to a highly flame-retardant cable protection pipe with metallocene polyolefin as the core resin component and a co-extruded composite double-layer structure, and its preparation method. Background Technology
[0002] Cable protection conduits are widely used in municipal power corridors, communication lines, rail transit, industrial plants, and building cable laying scenarios. Their main function is to provide mechanical protection for cables, isolate them from external impacts, and reduce the risk of cables getting damp and chemically corroded. As cable laying environments become increasingly complex, cable protection conduits, in addition to requiring basic ring stiffness, impact resistance, and weather resistance, also need to possess high flame-retardant properties to reduce the risk of flame spread within cable channels.
[0003] Existing cable protection pipes are mostly made of polyethylene, polypropylene, polyvinyl chloride, or ordinary polyolefin composite materials. While polyvinyl chloride has some flame retardancy, it may produce a lot of smoke and acidic gases when burning, posing a safety hazard in enclosed or semi-enclosed cable tunnel environments. Ordinary polyethylene and polypropylene have good processability and corrosion resistance, but their low oxygen index makes them prone to dripping and spreading during combustion, making them unsuitable for use in high flame-retardant environments.
[0004] To improve the flame-retardant properties of polyolefin cable protection pipes, existing technologies typically involve adding large amounts of magnesium hydroxide, aluminum hydroxide, ammonium polyphosphate, melamine salts, or intumescent flame retardants to the polyolefin matrix. However, these flame retardants are generally highly polar inorganic or phosphorus- and nitrogen-containing components, while the polyolefin matrix is a non-polar material, resulting in poor interfacial compatibility. When the amount of flame retardant added is high, the material is prone to problems such as decreased melt flowability, filler agglomeration, rough product surface, decreased impact strength, and decreased elongation at break. For cable protection pipes that need to withstand external soil pressure, construction dragging, low-temperature impact, and long-term service deformation, simply increasing the amount of flame retardant added does not yield a product with stable overall performance.
[0005] Furthermore, traditional single-layer flame-retardant pipes typically require the uniform addition of a large amount of flame retardant throughout the entire pipe wall, which significantly weakens the overall toughness and melt processing stability of the pipe. While using a conventional double-layer structure, separating the flame-retardant layer from the load-bearing layer can reduce the flame retardant content in the load-bearing layer, insufficient compatibility between the different layers can easily lead to interlayer delamination, thermal expansion and contraction cracking, or interface failure after long-term service. Relying on adhesive layers for interlayer bonding increases production processes and material costs; additionally, the adhesive layer itself may become a weak point in high-temperature or humid environments.
[0006] Metallocene polyolefins are suitable as important resin components in high-toughness polyolefin composites due to their narrow molecular weight distribution, uniform comonomer distribution, good low-temperature toughness, and good melt stability. However, constructing cable protection pipe systems around metallocene polyolefins that balance load-bearing capacity, flame retardancy, compatibility, and co-extrusion interface stability still requires targeted formulation and process design.
[0007] Therefore, there is an urgent need to provide a high flame-retardant cable protection pipe and its preparation method, so that while maintaining high flame-retardant performance, it also has high tensile strength, elongation at break, impact strength, ring stiffness and stable interlayer bonding performance. Summary of the Invention
[0008] The technical problem to be solved by the present invention is to provide a high flame-retardant cable protection pipe with metallocene polyolefin as the core component and its preparation method, so as to solve the problems of existing high-filled flame-retardant polyolefin cable protection pipes, such as difficulty in balancing flame retardant performance and mechanical toughness, poor dispersion of flame retardant, unstable interface bonding of double-layer pipes, and easy structural damage of intumescent flame retardant components during long-term high-shear processing.
[0009] To achieve the above objectives, the present invention provides the following technical solution: a high flame-retardant cable protection pipe, wherein the high flame-retardant cable protection pipe comprises a load-bearing inner layer and a flame-retardant outer layer that are coaxially arranged and formed into an integral structure by co-extrusion composite.
[0010] The load-bearing inner layer is mainly used to provide the pipe with impact resistance, tensile properties, ring stiffness, and construction toughness. The raw materials of the load-bearing inner layer, by weight, include: 32-45 parts of metallocene linear low-density polyethylene, 28-40 parts of polypropylene, 8-15 parts of metallocene ethylene-α-olefin copolymer, 8-18 parts of inorganic reinforcing filler, 2-5 parts of maleic anhydride-grafted metallocene polyolefin, and 0.5-2.0 parts of a first processing aid.
[0011] The flame-retardant outer layer is mainly used to enhance the flame-retardant, charring, smoke-suppressing, and flame-spreading resistance of the pipe's outer surface. The raw materials for the flame-retardant outer layer, by weight, include: 20-32 parts of metallocene linear low-density polyethylene, 8-16 parts of metallocene ethylene-α-olefin copolymer, 8-18 parts of polypropylene, 40-55 parts of interface-compatible composite flame-retardant masterbatch, 1-4 parts of boron-based charring synergist, 0.5-2.0 parts of organosilicon charring aid, and 0.5-2.0 parts of a second processing aid.
[0012] The interface-compatible composite flame retardant masterbatch comprises a phosphorus-nitrogen intumescent flame retardant component, magnesium hydroxide, maleic anhydride-grafted metallocene polyolefin carrier, and a silane coupling agent. By pre-forming the flame retardant component into a masterbatch, the dispersibility of the flame retardant in the metallocene polyolefin matrix can be improved, and agglomeration, moisture absorption, and processing fluctuations caused by direct powder addition can be reduced.
[0013] The interface-compatible composite flame retardant masterbatch is prepared through the following steps: P1. The phosphorus-nitrogen intumescent flame retardant component and magnesium hydroxide are dried separately. The dried phosphorus-nitrogen intumescent flame retardant component and magnesium hydroxide are added to a high-speed mixing device for premixing to obtain a flame retardant premix. P2. Under stirring conditions, a silane coupling agent solution is sprayed onto the surface of the flame-retardant premix, and surface modification is carried out at 80℃-105℃ to obtain a surface-modified flame-retardant mixture. P3. The surface-modified flame retardant mixture is melt-blended with maleic anhydride-grafted metallocene polyolefin carrier, and then extruded, cooled and pelletized to obtain the interface-compatible composite flame retardant masterbatch.
[0014] The thickness of the flame-retardant outer layer is 18%-35% of the total wall thickness of the high flame-retardant cable protection pipe, which helps to achieve a balance between flame-retardant protection capability and the overall mechanical properties of the pipe.
[0015] Preferably, the metallocene linear low-density polyethylene is a metallocene-catalyzed ethylene-1-hexene copolymer and / or ethylene-1-octene copolymer. The metallocene linear low-density polyethylene has a density of 0.910 g / cm³-0.935 g / cm³ and a melt flow rate of 0.5 g / 10 min-3.5 g / 10 min under test conditions of 190°C and 2.16 kg. The metallocene ethylene-α-olefin copolymer is preferably a metallocene ethylene-1-octene copolymer with a density of 0.860 g / cm³-0.900 g / cm³ and a melt flow rate of 0.5 g / 10 min-5.0 g / 10 min under test conditions of 190°C and 2.16 kg.
[0016] Preferably, the polypropylene in the load-bearing inner layer comprises at least one of homopolymer polypropylene and impact copolymer polypropylene. The inorganic reinforcing filler comprises at least one of calcium carbonate, talc, wollastonite, and mica powder. The median particle size D50 of the inorganic reinforcing filler is 1μm-8μm, and the surface of the inorganic reinforcing filler is modified by at least one of stearic acid, titanate coupling agent, or silane coupling agent.
[0017] Preferably, the raw materials of the interface-compatible composite flame retardant masterbatch include, by weight: 40-52 parts of ammonium polyphosphate, 8-16 parts of melamine polyphosphate, 5-12 parts of polyol charring agent, 18-30 parts of magnesium hydroxide, 8-15 parts of maleic anhydride-grafted metallocene polyolefin, 0.5-1.5 parts of silane coupling agent, and 0.5-2.0 parts of organosilicon processing aid.
[0018] Preferably, the ammonium polyphosphate has a degree of polymerization of not less than 1000 and a median particle size D50 of 5μm-18μm; the magnesium hydroxide has a median particle size D50 of 0.8μm-4.0μm.
[0019] Preferably, the metallocene polyolefin component of the load-bearing inner layer and the metallocene polyolefin component of the flame-retardant outer layer diffuse into each other in a co-extruded molten state, forming an apparent interface component transition zone at the continuous molten bonding interface. The thickness of the apparent interface component transition zone along the radial direction of the high flame-retardant cable protection pipe is 20μm-150μm, and no independent adhesive layer is provided between the load-bearing inner layer and the flame-retardant outer layer.
[0020] Preferably, the tensile strength of the load-bearing inner layer material is not less than 18 MPa, and the elongation at break is not less than 500%.
[0021] The present invention also provides a method for preparing the high flame-retardant cable protection tube, comprising the following steps: S1. Weigh the phosphorus-nitrogen intumescent flame retardant component, magnesium hydroxide, maleic anhydride-grafted metallocene polyolefin and silane coupling agent according to the predetermined ratio, and prepare an interface-compatible composite flame retardant masterbatch. S2. According to the raw material ratio of the load-bearing inner layer, metallocene linear low-density polyethylene, polypropylene, metallocene ethylene-α-olefin copolymer, inorganic reinforcing filler, maleic anhydride grafted metallocene polyolefin and the first processing aid are mixed to obtain the inner layer mixture. S3. According to the raw material ratio of the flame-retardant outer layer, metallocene linear low-density polyethylene, metallocene ethylene-α-olefin copolymer, polypropylene, boron-based char-forming synergist, organosilicon char-forming aid and second processing aid are mixed to obtain the outer layer matrix mixture. S4. The inner layer mixture is added to the inner layer extruder, the outer layer matrix mixture is added to the outer layer extruder, and the interface-compatible composite flame retardant masterbatch is added to the outer layer extruder through a side feeding device located in the mixing section after the outer layer matrix resin has been plasticized, so as to shorten the thermomechanical process of the flame retardant in the extruder and protect the structure of the intumescent flame retardant component. S5. The inner melt and the outer melt are fed into the co-extrusion die and combined through the annular flow channel to form a tube blank; S6. The tube blank is sequentially subjected to vacuum sizing, segmented cooling, traction and cutting to obtain the high flame-retardant cable protection tube.
[0022] Compared with the prior art, the present invention provides a high flame-retardant cable protection pipe and its preparation method, which has the following beneficial effects: by designing the pipe as a co-extruded composite structure of a load-bearing inner layer and a flame-retardant outer layer, the load-bearing inner layer mainly undertakes the mechanical support function of the pipe, and the flame-retardant outer layer mainly undertakes the flame-retardant protection function, thus avoiding the problem of reduced toughness of the entire pipe wall caused by high filling of flame retardant in traditional single-layer flame-retardant pipes.
[0023] This invention introduces metallocene polyolefin components into both the load-bearing inner layer and the flame-retardant outer layer, enabling the two layers to have good segment compatibility and diffusion ability in the co-extruded molten state. This results in the formation of a continuous molten bonding interface and a transition zone of apparent interface components without an adhesive layer, thereby improving the interlayer bonding stability of the double-layer pipe during long-term service.
[0024] This invention uses maleic anhydride-grafted metallocene polyolefin as a compatibility component, which improves the interfacial bonding between the inorganic reinforcing filler and the load-bearing inner polyolefin matrix on the one hand, and improves the interfacial compatibility between the phosphorus-nitrogen intumescent flame retardant component, magnesium hydroxide and the flame retardant outer polyolefin matrix on the other hand, thereby taking into account both flame retardant performance and mechanical properties.
[0025] This invention pre-forms an interface-compatible composite flame retardant masterbatch by combining phosphorus-nitrogen intumescent flame retardant components, magnesium hydroxide, silane coupling agent, and maleic anhydride-grafted metallocene polyolefin carrier. This can improve the uniformity of flame retardant dispersion, reduce powder agglomeration and moisture absorption, and improve the extrusion stability of pipes.
[0026] This invention introduces interface-compatible composite flame retardant masterbatch into the mixing section after the outer layer matrix resin has been plasticized in the outer layer extruder via a side feeding method. This shortens the thermomechanical process of the flame retardant in the extruder, reduces the risk of structural damage of the intumescent flame retardant component under high temperature and high shear conditions, and enables the outer layer flame retardant system to form a more continuous and denser intumescent char layer during combustion.
[0027] This invention improves the strength and crack resistance of the char layer of the flame-retardant outer layer by the synergistic effect of boron-based char-forming synergists and organosilicon char-forming aids, thereby reducing the risk of dripping and flame spread during combustion. Attached Figure Description
[0028] Figure 1 This is a scanning electron microscope (SEM) image of the interface between the load-bearing inner layer and the flame-retardant outer layer of the pipe section in Embodiment 2 of the present invention. Figure 2 This is a scanning electron microscope (SEM) image of the interface between the load-bearing inner layer and the flame-retardant outer layer of the pipe section in Comparative Example 4 of this invention. Figure 3 This is a scanning electron microscope (SEM) image of the frozen section of the flame-retardant outer layer material in Embodiment 2 of the present invention; Figure 4This is a scanning electron microscope (SEM) image of the frozen section of the flame-retardant outer layer material of Comparative Example 2 of the present invention. Detailed Implementation
[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0030] Please see Figures 1-4 This invention provides a technical solution for a high flame-retardant cable protection pipe and its preparation method: In the following examples, metallocene linear low-density polyethylene is denoted as mLLDPE, metallocene ethylene-α-olefin copolymer is denoted as mPOE, maleic anhydride-grafted metallocene polyolefin is denoted as MAH-g-mPO, ammonium polyphosphate is denoted as APP, melamine polyphosphate is denoted as MPP, and magnesium hydroxide is denoted as MH.
[0031] I. Main Raw Materials mLLDPE is selected from metallocene-catalyzed ethylene-1-octene copolymers with a density of 0.918 g / cm³-0.928 g / cm³ and a melt mass flow rate of 1.0 g / 10 min-2.5 g / 10 min.
[0032] The mPOE used is a metallocene ethylene-1-octene copolymer with a density of 0.870 g / cm³-0.890 g / cm³ and a melt mass flow rate of 1.0 g / 10 min-3.0 g / 10 min.
[0033] The polypropylene used is either impact copolymer polypropylene or homopolymer polypropylene.
[0034] Inorganic reinforcing fillers are selected from surface-modified talc, surface-modified calcium carbonate, or wollastonite, with a D50 of 1μm-8μm.
[0035] The aggregation degree of the APP is no less than 1000, and the D50 is 5μm-18μm.
[0036] The D50 of MH is 0.8μm-4.0μm.
[0037] The silane coupling agent selected is γ-aminopropyltriethoxysilane or vinyltrimethoxysilane.
[0038] Zinc borate is selected as the boron-based char-forming synergist.
[0039] The organosilicon carbonization aid is selected from ultra-high molecular weight polysiloxane or silicone masterbatch.
[0040] The first and second processing aids include antioxidants, lubricants, light stabilizers, and carbon black. The antioxidants are a combination of hindered phenolic antioxidants and phosphite antioxidants.
[0041] Example 1 1. Preparation of interfacially compatible composite flame retardant masterbatch Weigh the following raw materials by weight: APP 40 parts, MPP 8 parts, dipentaerythritol 5 parts, MH 18 parts, MAH-g-mPO 8 parts, silane coupling agent 0.5 parts, organosilicon processing aid 0.5 parts.
[0042] The specific steps are as follows: P1. APP, MPP, dipentaerythritol and MH were dried at 90°C for 3 hours, and then added to a high-speed mixer and mixed at 800 r / min for 8 minutes to obtain flame retardant premix. P2. Prepare a silane coupling agent solution by mixing silane coupling agent, ethanol and water in a mass ratio of 1:8:1. Spray the solution onto the surface of the flame retardant premix under stirring. Continue mixing at 80°C for 15 minutes to obtain a surface-modified flame retardant mixture. P3. The surface-modified flame retardant mixture, MAH-g-mPO, and organosilicon processing aids were added to a co-rotating parallel twin-screw extruder for melt mixing. The twin-screw extruder had a length-to-diameter ratio of 36:1, a screw speed of 180 r / min, and an extrusion temperature of 155℃-170℃. After extrusion, cooling, and pelletizing, an interfacially compatible composite flame retardant masterbatch was obtained.
[0043] 2. Preparation of high flame-retardant cable protection pipe The load-bearing inner layer material, by weight, is as follows: 32 parts mLLDPE, 28 parts polypropylene, 8 parts mPOE, 8 parts surface-modified talc, 2 parts MAH-g-mPO, and 0.5 parts first processing aid.
[0044] The flame-retardant outer layer material is as follows, by weight: 20 parts mLLDPE, 8 parts mPOE, 8 parts polypropylene, 40 parts interface-compatible composite flame retardant masterbatch, 1 part zinc borate, 0.5 parts organosilicon charring aid, and 0.5 parts secondary processing aid.
[0045] The preparation steps are as follows: S1. Preparation of interfacially compatible composite flame retardant masterbatch; S2. Add the raw materials of the load-bearing inner layer to a high-speed mixer and mix to obtain the inner layer mixture; S3. Add all raw materials except for the interface-compatible composite flame-retardant masterbatch to a high-speed mixer and mix to obtain the outer layer matrix mixture; S4. Add the inner layer mixture to the inner layer extruder, add the outer layer matrix mixture to the outer layer extruder, and add the interface-compatible composite flame retardant masterbatch through the side feeding device of the mixing section after the outer layer matrix resin has been plasticized in the outer layer extruder. The side feeding position is located at 45% of the effective length of the screw of the outer layer extruder. S5. The inner and outer melts enter the co-extrusion die, the temperature of the co-extrusion die is 175℃, and the temperature difference between the inner and outer melts is controlled within 10℃. S6. The tube blank is vacuum sizing, segmented cooling, traction and cutting to obtain a high flame-retardant cable protection tube.
[0046] In this embodiment, the thickness of the flame-retardant outer layer is 18% of the total wall thickness of the pipe, the vacuum degree of vacuum sizing is -0.03MPa, the cooling water temperature is 30℃, and the traction speed is 3.0m / min.
[0047] Example 2 1. Preparation of interfacially compatible composite flame retardant masterbatch Weigh the following raw materials by weight: APP 46 parts, MPP 12 parts, dipentaerythritol 8 parts, MH 24 parts, MAH-g-mPO 12 parts, silane coupling agent 1.0 part, organosilicon processing aid 1.2 parts.
[0048] The specific steps are as follows: P1. APP, MPP, dipentaerythritol and MH were dried at 95°C for 3 hours, and then added to a high-speed mixer and mixed at 1000 r / min for 10 minutes to obtain flame retardant premix. P2. Prepare a silane coupling agent solution by mixing silane coupling agent, ethanol and water in a mass ratio of 1:8:1. Spray the solution onto the surface of the flame retardant premix under stirring. Continue mixing at 95°C for 18 minutes to obtain a surface-modified flame retardant mixture. P3. The surface-modified flame retardant mixture, MAH-g-mPO, and organosilicon processing aids were added to a co-rotating parallel twin-screw extruder for melt mixing. The twin-screw extruder had a length-to-diameter ratio of 44:1, a screw speed of 260 r / min, and an extrusion temperature of 160℃-175℃. After extrusion, cooling, and pelletizing, an interfacially compatible composite flame retardant masterbatch was obtained.
[0049] 2. Preparation of high flame-retardant cable protection pipe The load-bearing inner layer material, by weight, is as follows: 38 parts mLLDPE, 34 parts polypropylene, 12 parts mPOE, 13 parts surface-modified talc, 3.5 parts MAH-g-mPO, and 1.2 parts first processing aid.
[0050] The flame-retardant outer layer material is as follows, by weight: 26 parts mLLDPE, 12 parts mPOE, 13 parts polypropylene, 48 parts interface-compatible composite flame retardant masterbatch, 2.5 parts zinc borate, 1.2 parts organosilicon charring aid, and 1.2 parts secondary processing aid.
[0051] The preparation method is basically the same as in Example 1, except that: the side feeding position is located at 58% of the effective length of the outer extruder screw; the co-extrusion die temperature is 188℃; the vacuum sizing vacuum degree is -0.055MPa; the cooling water temperature is 22℃; the traction speed is 1.5m / min; and the flame-retardant outer layer thickness is 26% of the total wall thickness of the pipe.
[0052] Example 3 1. Preparation of interfacially compatible composite flame retardant masterbatch Weigh the following raw materials by weight: APP 52 parts, MPP 16 parts, dipentaerythritol 12 parts, MH 30 parts, MAH-g-mPO 15 parts, silane coupling agent 1.5 parts, organosilicon processing aid 2.0 parts.
[0053] The specific steps are as follows: P1. APP, MPP, dipentaerythritol and MH were dried at 105℃ for 2.5 hours, and then added to a high-speed mixer and mixed at 1200r / min for 12 minutes to obtain flame retardant premix. P2. Prepare a silane coupling agent solution by mixing silane coupling agent, ethanol and water in a mass ratio of 1:8:1. Spray the solution onto the surface of the flame retardant premix under stirring. Continue mixing at 105°C for 20 minutes to obtain a surface-modified flame retardant mixture. P3. The surface-modified flame retardant mixture, MAH-g-mPO, and organosilicon processing aids were added to a co-rotating parallel twin-screw extruder for melt mixing. The twin-screw extruder had a length-to-diameter ratio of 48:1, a screw speed of 350 r / min, and an extrusion temperature of 165℃-180℃. After extrusion, cooling, and pelletizing, an interfacially compatible composite flame retardant masterbatch was obtained.
[0054] 2. Preparation of high flame-retardant cable protection pipe The load-bearing inner layer material, by weight, is as follows: 45 parts mLLDPE, 40 parts polypropylene, 15 parts mPOE, 18 parts surface-modified wollastonite, 5 parts MAH-g-mPO, and 2.0 parts first processing aid.
[0055] The flame-retardant outer layer material is as follows, by weight: 32 parts mLLDPE, 16 parts mPOE, 18 parts polypropylene, 55 parts interface-compatible composite flame retardant masterbatch, 4 parts zinc borate, 2.0 parts organosilicon charring aid, and 2.0 parts secondary processing aid.
[0056] The preparation method is basically the same as in Example 1, except that: the side feeding position is located at 70% of the effective length of the outer extruder screw; the co-extrusion die temperature is 200℃; the vacuum sizing vacuum degree is -0.08MPa; the cooling water temperature is 15℃; the traction speed is 0.3m / min; and the flame-retardant outer layer thickness is 35% of the total wall thickness of the pipe.
[0057] Example 4 The preparation method of the interface-compatible composite flame retardant masterbatch is the same as that in Example 2.
[0058] The load-bearing inner layer material, by weight, is as follows: 40 parts mLLDPE, 35 parts polypropylene, 13 parts mPOE, 15 parts surface-modified calcium carbonate, 4 parts MAH-g-mPO, and 1.5 parts first processing aid.
[0059] The flame-retardant outer layer material is as follows, by weight: 28 parts mLLDPE, 14 parts mPOE, 15 parts polypropylene, 50 parts interface-compatible composite flame retardant masterbatch, 3 parts zinc borate, 1.5 parts organosilicon charring aid, and 1.5 parts secondary processing aid.
[0060] The preparation method is the same as in Example 2, except that: the thickness of the flame-retardant outer layer is 30% of the total wall thickness of the pipe, the temperature of the co-extrusion die is 190℃, and the traction speed is 1.0m / min.
[0061] Example 5 The interface-compatible composite flame retardant masterbatch and the inner and outer layer formulations are the same as in Example 2.
[0062] The preparation method is basically the same as in Example 2, except that: the side feeding position is located at 45% of the effective length of the outer extruder screw, the co-extrusion die temperature is 185°C, and the thickness of the flame-retardant outer layer is 26% of the total wall thickness of the pipe.
[0063] Example 6 The interface-compatible composite flame retardant masterbatch and the inner and outer layer formulations are the same as in Example 2.
[0064] The preparation method is basically the same as in Example 2, except that: the side feeding position is located at 70% of the effective length of the outer extruder screw, the co-extrusion die temperature is 190°C, and the flame-retardant outer layer thickness is 26% of the total wall thickness of the pipe.
[0065] Comparative Example 1 was made by replacing mLLDPE in the load-bearing inner layer and flame-retardant outer layer with ordinary linear low-density polyethylene in equal amounts. Other resins, flame-retardant masterbatches, fillers, additives, outer layer thickness and processing technology were the same as in Example 2.
[0066] Comparative Example 2: The MAH-g-mPO in the interface-compatible composite flame retardant masterbatch was replaced with an equal amount of ordinary polyethylene carrier, while the MAH-g-mPO in the load-bearing inner layer remained unchanged. All other components and processes were the same as in Example 2.
[0067] Comparative Example 3 differs only in that the interface-compatible composite flame-retardant masterbatch was changed from being fed laterally into the mixing section after the outer matrix resin of the outer extruder was plasticized, to being added together with the outer matrix mixture from the main feed port. Other raw material ratios, extrusion temperatures, co-extrusion die temperatures, and flame-retardant outer layer thicknesses are the same as in Example 2.
[0068] Comparative Example 4 was modified by changing the molding method from double-layer co-extrusion composite to first extruding the load-bearing inner layer and cooling it for shaping, and then extruding a flame-retardant outer layer on its outer surface for secondary coating. The other raw material ratios, flame-retardant outer layer thickness and processing temperature were the same as in Example 2.
[0069] Comparative Example 5: only the zinc borate and organosilicon char-forming aid in the flame-retardant outer layer were removed and replaced with an equal amount of mLLDPE. All other raw materials and processes were the same as in Example 2.
[0070] Performance testing I. Sample Preparation The pipes prepared in Examples 1-6 and Comparative Examples 1-5 were numbered FRP-01 to FRP-11, respectively. Wherein: FRP-01 corresponds to Example 1; FRP-02 corresponds to Example 2; FRP-03 corresponds to Example 3; FRP-04 corresponds to Example 4; FRP-05 corresponds to Example 5; FRP-06 corresponds to Example 6; FRP-07 has a response ratio of 1; FRP-08 has a response ratio of 2; FRP-09 has a response ratio of 3; FRP-10 has a response ratio of 4; FRP-11 has a response ratio of 5.
[0071] Each group of pipes was tested after being placed at room temperature for 48 hours. For flame retardancy, mechanical properties, impact performance, ring stiffness, and interlaminar bonding performance, at least 5 samples were tested, and the average value was taken as the result.
[0072] II. Testing Methods 1. Oxygen Index Test The oxygen index was determined according to GB / T 2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test". A higher oxygen index indicates that the material requires a higher oxygen concentration to sustain combustion in an oxygen-nitrogen mixed atmosphere, and thus has better flame retardant properties.
[0073] 2. Vertical Burning Test Vertical burning performance was tested according to GB / T 2408-2021 "Determination of Burning Performance of Plastics - Horizontal and Vertical Methods", and the material burning rating was recorded. V-0 rating is superior to V-1 rating, and V-1 rating is superior to V-2 rating.
[0074] 3. Tensile property test The tensile properties of the load-bearing inner layer material and pipe slices were tested in accordance with GB / T 1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics", and the tensile strength and elongation at break were recorded.
[0075] 4. Impact strength test of simply supported beam pipe The impact strength of simply supported beam pipes was tested according to GB / T 18743.1-2022 and GB / T 18743.2-2022. Higher impact strength indicates better resistance to construction impacts and low-temperature brittle fracture.
[0076] 5. Ring stiffness test Ring stiffness was determined according to GB / T 9647-2015 "Determination of Ring Stiffness of Thermoplastic Pipes". Higher ring stiffness indicates a stronger resistance to external radial compressive deformation of the pipe.
[0077] 6. Interlayer bonding performance test The interlayer bonding performance was evaluated using a 90° peel test. Strip samples were cut axially from the pipe. After manually separating the flame-retardant outer layer from the load-bearing inner layer at the starting end, the strips were peeled at a speed of 50 mm / min on a universal testing machine, and the average peel strength was recorded. Higher peel strength indicates a more stable bond between the load-bearing inner layer and the flame-retardant outer layer.
[0078] 7. Observation of the transition area of interface components in the interface appearance Pipe cross-section samples were prepared by cryosectioning. After staining, scanning electron microscopy combined with energy dispersive spectroscopy was used to scan the phosphorus concentration along the radial direction of the pipe across the interface between the load-bearing inner layer and the flame-retardant outer layer. The radial distance corresponding to the decrease of the phosphorus signal from 90% to 10% of the stable value of the flame-retardant outer layer was defined as the thickness of the interface composition transition zone. At least 5 locations were randomly selected for each sample, and the average value was taken to measure the thickness of the interface composition transition zone.
[0079] Test Results Table 1. Test results of flame retardant performance and char layer stability
[0080] As shown in Table 1, the oxygen index of Examples 1-6 is not lower than 32.8%, and all reach V-0 level, indicating that within the specified range, the flame-retardant outer layer can form effective flame-retardant protection. Among them, the oxygen index of Examples 2-4 is between 37.4% and 40.6%, and the char layer is continuous and dense, showing better flame-retardant effect.
[0081] The oxygen indices of Comparative Examples 2 and 3 were 31.6% and 30.8%, respectively, both significantly lower than the 37.4% of Example 2. However, the reasons for the decrease in flame retardant performance in the two examples were different. In Comparative Example 2, the MAH-g-mPO in the interface-compatible composite flame retardant masterbatch was replaced by a common polyethylene carrier, resulting in a decrease in the interfacial compatibility between the polar flame retardant component and the non-polar polyolefin matrix. This led to uneven dispersion of the flame retardant and easy formation of agglomeration defects, thereby reducing the uniformity of the char layer and the flame retardant stability. In Comparative Example 3, under the same flame retardant masterbatch composition, the side feeding was changed to the main feeding port, causing the intumescent flame retardant component to undergo a longer period of high temperature and high shear in the extruder. This resulted in structural damage or decreased reactivity of some flame retardant components, manifested as insufficient foaming of the char layer and reduced flame retardant efficiency after combustion.
[0082] In Comparative Example 5, after removing zinc borate and organosilicon char-forming aids, the char layer became loose and cracked, and the oxygen index decreased to 29.4%, indicating that boron-based char-forming synergists and organosilicon char-forming aids have a significant effect on improving the strength of the char layer.
[0083] Table 2. Test results of mechanical properties, impact properties, and ring stiffness.
[0084] As shown in Table 2, in Examples 1-6, the tensile strength of the load-bearing inner layer is not less than 18 MPa, and the elongation at break is not less than 500%, which supports the requirements for high strength and toughness of the load-bearing inner layer within the specified range. Among them, Example 2 shows the best performance, with a tensile strength of 22.9 MPa, an elongation at break of 642%, and a pipe simply supported beam impact strength of 32.5 kJ·m. - ² indicates that the formulation in the middle region has a good balance in terms of strength, toughness, and processability.
[0085] In Comparative Example 1, after replacing mLLDPE with ordinary linear low-density polyethylene, the elongation at break of the load-bearing inner layer decreased to 382%, and the impact strength decreased to 18.4 kJ·m. - ² indicates that metallocene linear low-density polyethylene plays an important role in maintaining the toughness of highly filled composite systems.
[0086] In Comparative Example 2, after the flame retardant masterbatch carrier was replaced with ordinary polyethylene, the interfacial compatibility of the flame retardant decreased, and material defects increased, resulting in a significant reduction in elongation at break and impact strength. Compared with Comparative Example 3, Comparative Example 2 not only showed a decrease in flame retardant performance but also a significant loss in mechanical toughness, further illustrating that its main failure cause lies in insufficient dispersion and interfacial bonding of the flame retardant, rather than simply a problem with the thermal stability of the flame retardant components.
[0087] In Comparative Example 5, although the mechanical properties did not decrease after the removal of boron-based and organosilicon synergists, the flame retardant properties deteriorated significantly, indicating that simply increasing the proportion of the matrix resin cannot replace the synergistic flame retardant effect of boron-based char-forming synergists and organosilicon char-forming aids.
[0088] Table 3 Test results of interlayer bonding performance and interface structure
[0089] As shown in Table 3, Examples 1-6 all formed apparent interfacial component transition regions in the range of 20μm-150μm, and their average peel strength was significantly higher than that of Comparative Example 4. The apparent interfacial component transition region thickness of Example 2 was 86μm, and its average peel strength was 32.4 N·cm. - ¹ The interlayer failure mode is cohesive failure, indicating that the load-bearing inner layer and the flame-retardant outer layer are not simply physically bonded, but rather form a stable continuous molten bonding interface under co-extrusion melting state.
[0090] In Comparative Example 4, the pipe was prepared by first extruding the inner layer, cooling, and then coating the outer layer again. Although the raw material formula was the same as in Example 2, the two layers did not diffuse sufficiently into each other in the co-extruded molten state, resulting in an apparent interfacial component transition zone thickness of only 8 μm and an average peel strength of only 7.2 N·cm. - ¹, and obvious interface peeling occurs. This indicates that the co-extrusion melt-bonded interface is a key technical feature of this invention for improving the interlayer bonding stability of double-layer pipes.
[0091] Performance Result Analysis 1. Contribution of metallocene polyolefins to high-toughness load-bearing layers As can be seen from Example 2 and Comparative Example 1, under essentially the same conditions, after replacing mLLDPE with ordinary linear low-density polyethylene, the elongation at break of the load-bearing inner layer decreased from 642% to 382%, and the impact strength of the simply supported beam of the pipe decreased from 32.5 kJ·m. - ² decreased to 18.4 kJ·m - ², the average peel strength also increased from 32.4 N·cm. - ¹Decreased to 16.5 N·cm - ¹.
[0092] This indicates that metallocene linear low-density polyethylene not only improves the toughness of the load-bearing inner layer but also enhances the interfacial compatibility between the metallocene polyolefin components in the load-bearing inner layer and the flame-retardant outer layer. Since both layers contain metallocene polyolefin segments, a transition zone of apparent interfacial components is more easily formed during co-extrusion melt processing, thereby improving interlayer bonding stability.
[0093] 2. Contribution of interfacially compatible composite flame retardant masterbatch to flame retardant dispersibility Compared with Comparative Example 2, Example 2 only replaced MAH-g-mPO in the interface-compatible composite flame-retardant masterbatch with ordinary polyethylene carrier. Its oxygen index decreased from 37.4% to 31.6%, its vertical burning rating decreased from V-0 to V-1, and its impact strength decreased from 32.5 kJ·m. - ² decreased to 20.2 kJ·m - ².
[0094] The above results indicate that MAH-g-mPO not only acts as a resin carrier but also plays a role in the interfacial compatibility of flame retardants. Its maleic anhydride graft groups can improve the interfacial bonding between polar flame retardant components such as ammonium polyphosphate and magnesium hydroxide and the non-polar polyolefin matrix, reduce defects caused by flame retardant agglomeration, and thus simultaneously improve flame retardant stability and mechanical properties.
[0095] Furthermore, the main failure mechanism of Comparative Example 2 lies in insufficient interfacial compatibility. Ordinary polyethylene carriers lack grafting groups that can interact with polar flame-retardant components, making it difficult to effectively coat and disperse flame-retardant particles such as APP, MPP, and MH. After the flame retardant agglomerates, on the one hand, it causes uneven distribution of flame-retardant components in the outer flame-retardant layer, reducing the continuity of the expanded char layer during combustion; on the other hand, it forms stress concentration points within the material, leading to a decrease in elongation at break and impact strength. Therefore, Comparative Example 2 reflects a "decrease in overall performance caused by poor flame retardant dispersion and interfacial defects."
[0096] 3. The protective effect of the side-feeding process on the intumescent flame retardant components Compared with Comparative Example 3, Example 2 only changed the side feeding of the interface-compatible composite flame retardant masterbatch to the main feeding port. As a result, the oxygen index decreased from 37.4% to 30.8%, the vertical combustion rating decreased from V-0 to V-1, and the char layer foaming was insufficient after combustion.
[0097] This is because APP, MPP, and polyol charring agents in intumescent flame retardant systems may undergo localized decomposition, agglomeration, or decreased reactivity when exposed to high temperature and high shear conditions for extended periods. This invention addresses this by adding the composite flame retardant masterbatch laterally from the mixing section after the outer layer matrix resin in the outer extruder has been plasticized. This allows the masterbatch to enter the system in a region where the resin has melted and shear conditions are relatively controllable, thereby shortening the thermomechanical journey and maintaining the structural integrity of the intumescent flame retardant components.
[0098] Unlike Comparative Example 2, the composition of the interfacially compatible composite flame retardant masterbatch in Comparative Example 3 remained unchanged, with MAH-g-mPO still acting as the compatibility carrier. Therefore, its interlayer bonding performance and mechanical properties decreased relatively little. However, because the flame retardant masterbatch enters the extruder from the main feed port, the intumescent flame retardant components need to undergo a complete thermomechanical process from solid conveying, compression melting to homogenization extrusion. This significantly increases the residence time and shearing action, leading to damage to the structural integrity and char-forming foaming ability of some intumescent flame retardant components. Thus, Comparative Example 3 demonstrates "damage to the intumescent flame retardant system due to excessively long processing thermomechanical journey," and its failure path differs from that of Comparative Example 2, which shows "dispersion and agglomeration due to insufficient interfacial compatibility."
[0099] 4. Further distinction between the failure mechanisms of Comparative Example 2 and Comparative Example 3 Although the oxygen indices of Comparative Example 2 and Comparative Example 3 were 31.6% and 30.8% respectively, both of which were lower than the 37.4% of Example 2, and both ultimately showed a decrease in flame retardant performance, the technical problems they revealed were different.
[0100] The variable in Comparative Example 2 was replacing MAH-g-mPO in the interfacially compatible composite flame-retardant masterbatch with a common polyethylene carrier. The core impact was a decrease in the interfacial compatibility between the flame retardant and the polyolefin matrix. Because flame-retardant components such as APP, MPP, and MH have strong polarity, while the common polyethylene carrier lacks effective interfacial interaction groups, the flame-retardant components are more prone to agglomeration and uneven dispersion in the outer matrix. This type of defect not only weakens the uniformity of char layer formation during combustion but also becomes a stress concentration point in mechanical damage. Therefore, Comparative Example 2 simultaneously exhibited a decrease in oxygen index, uneven char layer, and a decrease in impact strength and elongation at break.
[0101] The variable in Comparative Example 3 was the feeding method, which changed from side feeding in the mixing section after the outer matrix resin had completed plasticization to feeding through the main feed port. The core impact was a significant extension of the thermomechanical process experienced by the flame-retardant components. In this comparative example, the compatibility system of the flame-retardant masterbatch was not eliminated, but the residence time of intumescent flame-retardant components such as APP, MPP, and polyol charring agents in the high-temperature, high-shear environment increased, potentially leading to premature heating, structural damage, or reduced charring reactivity of some components. Therefore, Comparative Example 3 mainly exhibited insufficient foaming of the char layer after combustion and a decrease in flame-retardant efficiency, while its mechanical properties and interlayer bonding performance were better maintained compared to Comparative Example 2.
[0102] Therefore, Comparative Example 2 is used to demonstrate the importance of the MAH-g-mPO compatible carrier for the dispersion and overall performance of the flame retardant; Comparative Example 3 is used to demonstrate the importance of the side-feeding process for maintaining the structure of the intumescent flame retardant component and its flame retardant efficiency. Although both lead to a decrease in the oxygen index, from the perspectives of material structure, processing, and performance, they correspond to different failure mechanisms, and can support the necessity and synergy of the technical solution of this invention from different angles.
[0103] 5. Contribution of the co-extruded melt-bonded interface to the stability of double-layer pipes Compared to Comparative Example 4, Example 2 used the same raw material formulation, but the molding method was changed from double-layer co-extrusion to secondary coating after cooling the inner layer. Its apparent interfacial component transition zone thickness was only 8 μm, and the average peel strength was only 7.2 N·cm. - ¹, and obvious interface peeling occurs.
[0104] The apparent interfacial component transition zone thickness in Example 2 was 86 μm, and the average peel strength was 32.4 N·cm. - ¹, the interlayer failure mode is cohesive failure. This result indicates that the "mutual diffusion in the co-extruded molten state" defined in the claims is not a description of a typical layered structure, but a key structural feature that can directly improve the interfacial bonding stability of double-layer pipes.
[0105] 6. Synergistic effect of boron-based char-forming synergists and organosilicon char-forming aids Compared with Comparative Example 5, Comparative Example 5, after removing zinc borate and organosilicon char-forming aids, although the tensile strength and impact strength did not decrease significantly, the oxygen index decreased from 37.4% to 29.4%, the vertical combustion rating decreased from V-0 to V-1, and the char layer changed from continuous and dense to loose and cracked.
[0106] This indicates that boron-based char-forming synergists and organosilicon char-forming aids primarily contribute to the char layer reinforcement during the combustion process of the flame-retardant outer layer. The boron-based components help improve the ceramization and anti-dripping ability of the char layer, while the organosilicon components help enhance the continuity and crack resistance of the char layer. Together, they enable the flame-retardant outer layer to form a more stable heat-insulating protective layer under flame conditions.
[0107] As can be seen from the above embodiments and comparative examples, the present invention does not simply add flame retardants to polyolefin pipes, but rather establishes a combined technical solution around metallocene polyolefins, namely, "high toughness of the load-bearing inner layer - efficient charring of the flame-retardant outer layer - compatibility of grafted metallocene polyolefins - lateral feeding to protect the flame-retardant system - interdiffusion at the co-extrusion melt interface".
[0108] Figure 1 In the figure, the left side represents the load-bearing inner layer, the right side represents the flame-retardant outer layer, and the middle area represents the interface bonding region formed by the molten co-extrusion of the two layers. As can be seen from the figure, the two layers exhibit a continuous transition structure without obvious cracks, voids, or interface delamination, indicating that a good molten bonding interface has been formed between the load-bearing inner layer and the flame-retardant outer layer.
[0109] Figure 2 In the figure, the left side is the load-bearing inner layer, and the right side is the flame-retardant outer layer. As can be seen from the figure, the interface between the two layers is clearly defined, with gaps, pores, and discontinuous areas in some areas, and no continuous interdiffusion structure is formed, indicating that the interlayer bonding effect of the secondary coating method after cooling is weak.
[0110] Figure 3 In the figure, the continuous phase is the metallocene polyolefin matrix, and the granular regions are the composite flame retardant components. As can be seen from the figure, the flame retardant particles are relatively uniformly dispersed, without obvious large-size agglomeration or interfacial debonding pores, indicating that the compatibility carrier can improve the interfacial bonding between the flame retardant components and the polyolefin matrix.
[0111] Figure 4 In the figure, numerous particle extraction holes, interfacial gaps, and localized agglomeration areas are visible. The cross-sectional structure is loose and has poor uniformity, indicating that after replacing the grafted compatibility carrier with ordinary polyethylene, the interfacial bonding and dispersion effect between the flame retardant component and the polyolefin matrix is significantly reduced.
[0112] The high flame-retardant cable protection pipe prepared by this invention can simultaneously achieve: an oxygen index of not less than 32.8%; a vertical combustion rating of V-0; a tensile strength of the load-bearing inner layer of not less than 18 MPa; an elongation at break of not less than 500% for the load-bearing inner layer; and a simply supported beam impact strength of 23.8 kJ·m. - ² or more; ring stiffness maintained at 8.2 kN·m - The thickness of the apparent interface component transition zone is 20μm-150μm; the average peel strength is significantly higher than that of the non-co-extruded composite structure.
[0113] Comparative Examples 2 and 3 further demonstrate that the MAH-g-mPO compatibility carrier and the side-feeding process in this invention function in two aspects: "interfacial dispersion stability" and "processing structure protection," respectively. MAH-g-mPO can improve the interfacial compatibility between the flame retardant and the polyolefin matrix, reducing flame retardant agglomeration and material defects. The side-feeding process can shorten the thermomechanical journey of the intumescent flame retardant component in the extruder, reducing its structural damage risk. Together with the metallocene polyolefin co-extrusion composite structure, boron-based charring synergists, and organosilicon charring aids, these components achieve a good balance between flame retardant performance, mechanical toughness, interlayer bonding stability, and industrial extrusion feasibility in the pipe material.
[0114] Therefore, this invention is suitable for applications with high requirements for flame retardancy and mechanical protection, such as municipal power pipelines, communication pipelines, rail transit, industrial plants and building cable laying.
Claims
1. A high flame-retardant cable protection pipe, characterized in that, It includes a load-bearing inner layer and a flame-retardant outer layer continuously covering the outer periphery of the load-bearing inner layer. The load-bearing inner layer and the flame-retardant outer layer are formed into an integral structure through a single co-extrusion composite, and there is no independent adhesive layer between the two. The raw materials of the load-bearing inner layer include, by weight: The composition includes 32-45 parts of metallocene linear low-density polyethylene, 28-40 parts of polypropylene, 8-15 parts of metallocene ethylene-α-olefin copolymer, 8-18 parts of inorganic reinforcing filler, 2-5 parts of maleic anhydride-grafted metallocene polyolefin, and 0.5-2.0 parts of first processing aid. The raw materials of the flame-retardant outer layer include, by weight: 20-32 parts of metallocene linear low-density polyethylene, 8-16 parts of metallocene ethylene-α-olefin copolymer, 8-18 parts of polypropylene, 40-55 parts of interface-compatible composite flame retardant masterbatch, 1-4 parts of boron-based charring synergist, 0.5-2.0 parts of organosilicon charring aid, and 0.5-2.0 parts of secondary processing aid. The interface-compatible composite flame retardant masterbatch includes ammonium polyphosphate, melamine polyphosphate, polyol charring agent, magnesium hydroxide, maleic anhydride-grafted metallocene polyolefin carrier, silane coupling agent, and organosilicon processing aid.
2. The high flame-retardant cable protection pipe according to claim 1, characterized in that: The metallocene linear low-density polyethylene is a metallocene-catalyzed ethylene-1-hexene copolymer and / or an ethylene-1-octene copolymer; The metallocene linear low-density polyethylene has a density of 0.910 g / cm³-0.935 g / cm³ and a melt mass flow rate of 0.5 g / 10 min-3.5 g / 10 min under test conditions of 190 °C and 2.16 kg. The metallocene ethylene-α-olefin copolymer is a metallocene ethylene-1-octene copolymer with a density of 0.860 g / cm³-0.900 g / cm³ and a melt mass flow rate of 0.5 g / 10 min-5.0 g / 10 min under test conditions of 190 °C and 2.16 kg.
3. The high flame-retardant cable protection pipe according to claim 1, characterized in that: The polypropylene in the load-bearing inner layer includes at least one of homopolymer polypropylene and impact copolymer polypropylene. The inorganic reinforcing filler includes at least one of calcium carbonate, talc, wollastonite, and mica powder; The median particle size D50 of the inorganic reinforcing filler is 1μm-8μm, and the surface of the inorganic reinforcing filler is modified by at least one of stearic acid, titanate coupling agent or silane coupling agent.
4. The high flame-retardant cable protection pipe according to claim 1, characterized in that: The raw materials of the interface-compatible composite flame retardant masterbatch include, by weight: Ammonium polyphosphate 40-52 parts, melamine polyphosphate 8-16 parts, polyol charring agent 5-12 parts, magnesium hydroxide 18-30 parts, maleic anhydride grafted metallocene polyolefin 8-15 parts, silane coupling agent 0.5-1.5 parts, and organosilicon processing aid 0.5-2.0 parts. The polyol charring agent includes at least one of pentaerythritol, dipentaerythritol, and starch-based charring agent.
5. A high flame-retardant cable protection pipe according to claim 4, characterized in that: The degree of polymerization of the ammonium polyphosphate is not less than 1000, and the median particle size D50 is 5μm-18μm; The median particle size D50 of the magnesium hydroxide is 0.8 μm-4.0 μm; The silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane.
6. The high flame-retardant cable protection pipe according to claim 1, characterized in that: A continuous interface bonding zone is formed between the load-bearing inner layer and the flame-retardant outer layer; a scanning electron microscope-energy dispersive spectroscopy (EDS) is used to perform a line scan of phosphorus element along the radial direction of the pipe across the continuous interface bonding zone, and the radial distance corresponding to the decrease of phosphorus element signal from 90% to 10% of the stable signal value of the flame-retardant outer layer is taken as the thickness of the apparent interface component transition zone, and the thickness of the apparent interface component transition zone is 20 μm to 150 μm.
7. The high flame-retardant cable protection pipe according to claim 1, characterized in that: The boron-based char-forming synergist includes at least one of zinc borate, anhydrous zinc borate, and magnesium borate. The organosilicon char-forming aid includes at least one of ultra-high molecular weight polysiloxane, organosilicon resin, and silicone masterbatch; The first processing aid and the second processing aid each independently include at least one of antioxidant, lubricant, light stabilizer and carbon black.
8. A high flame-retardant cable protection pipe according to claim 1, characterized in that: The load-bearing inner layer material is prepared into a standard sample under the same melting and processing conditions as the load-bearing inner layer of the pipe. The sample is tested in accordance with GB / T 1040.2-2022. The measured tensile strength is not less than 18 MPa and the elongation at break is not less than 500%.
9. A method for preparing a high flame-retardant cable protection tube as described in any one of claims 1-8, characterized in that, Includes the following steps: S1. Weigh out the following components by weight as defined in claim 4: ammonium polyphosphate, melamine polyphosphate, polyol charring agent, magnesium hydroxide, maleic anhydride-grafted metallocene polyolefin, silane coupling agent, and organosilicon processing aid; dry and premix the ammonium polyphosphate, melamine polyphosphate, polyol charring agent, and magnesium hydroxide; perform surface treatment with silane coupling agent; after drying to remove volatiles, melt-blend, cool, and granulate the mixture with maleic anhydride-grafted metallocene polyolefin and organosilicon processing aid to obtain an interface-compatible composite flame retardant masterbatch. S2. According to the raw material ratio of the load-bearing inner layer, metallocene linear low-density polyethylene, polypropylene, metallocene ethylene-α-olefin copolymer, inorganic reinforcing filler, maleic anhydride grafted metallocene polyolefin and the first processing aid are mixed to obtain the inner layer mixture. S3. According to the raw material ratio of the flame-retardant outer layer, metallocene linear low-density polyethylene, metallocene ethylene-α-olefin copolymer, polypropylene, boron-based char-forming synergist, organosilicon char-forming aid and second processing aid are mixed to obtain the outer layer matrix mixture. S4. Add the inner layer mixture to the inner layer extruder and the outer layer matrix mixture to the outer layer extruder; after the outer layer matrix mixture has been plasticized, add the interface-compatible composite flame-retardant masterbatch to the outer layer extruder through a side feeding device, wherein the side feeding device is located at a position 45% to 70% of the effective length of the screw, starting from the main feeding port of the outer layer extruder; S5. The inner melt and the outer melt are fed into the co-extrusion die and combined through the annular flow channel to form a tube blank; S6. The tube blank is sequentially subjected to vacuum sizing, segmented cooling, traction and cutting to obtain the high flame-retardant cable protection tube; The interface-compatible composite flame retardant masterbatch is prepared through the following steps: P1. The phosphorus-nitrogen intumescent flame retardant component and magnesium hydroxide are dried separately. The dried phosphorus-nitrogen intumescent flame retardant component and magnesium hydroxide are added to a high-speed mixing device for premixing to obtain a flame retardant premix. P2. Under stirring conditions, a silane coupling agent solution is sprayed onto the surface of the flame-retardant premix, and surface modification is carried out at 80℃-105℃ to obtain a surface-modified flame-retardant mixture. P3. The surface-modified flame retardant mixture is melt-blended with maleic anhydride-grafted metallocene polyolefin carrier, and then extruded, cooled and pelletized to obtain the interface-compatible composite flame retardant masterbatch. The thickness of the flame-retardant outer layer is 18%-35% of the total wall thickness of the high flame-retardant cable protection pipe.
10. The preparation method according to claim 9, characterized in that: In step S5, the temperature of the co-extrusion die head is 175℃-200℃, and the temperature difference between the inner melt and the outer melt when they enter the co-extrusion die head is no greater than 15℃. In step S6, the vacuum degree of vacuum sizing is -0.03MPa to -0.08MPa, the cooling water temperature is 15℃ to 30℃, and the traction speed is 0.3m / min to 3.0m / min. By adjusting the extrusion rates of the inner and outer extruders, the thickness of the flame-retardant outer layer is maintained at 18%-35% of the total wall thickness of the high flame-retardant cable protection pipe.